1999
DOI: 10.1063/1.124294
|View full text |Cite
|
Sign up to set email alerts
|

Indications of antiferromagnetic interlayer coupling in La2/3Ba1/3MnO3/LaNiO3 multilayers

Abstract: Multilayers consisting of the perovskite metallic oxides, ferromagnetic La2/3Ba1/3MnO3 (LBMO) and paramagnetic LaNiO3 (LNO) have been grown by ozone-assisted molecular beam epitaxy. Structural characterization using in situ reflection high-energy electron diffraction and high-resolution x-ray diffraction reveal a very high degree of crystalline order. Magnetization and hysteresis measurements show evidence of antiferromagnetic coupling between LBMO layers when the LNO spacer is 15 Å or less in thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Magnetic multilayer structures based on transition metals 1,2 and their compounds [1][2][3][4][5][6][7][8][9][10][11][12][13][14] have high potential for technological applications as their transport and magnetic properties can be controlled with the non-magnetic spacer layer thickness. However, to use these materials for applications, it is necessary to understand and control precisely the physical properties that depend on various parameters such as the layer materials, their thicknesses and the interfaces between them.…”
mentioning
confidence: 99%
“…Magnetic multilayer structures based on transition metals 1,2 and their compounds [1][2][3][4][5][6][7][8][9][10][11][12][13][14] have high potential for technological applications as their transport and magnetic properties can be controlled with the non-magnetic spacer layer thickness. However, to use these materials for applications, it is necessary to understand and control precisely the physical properties that depend on various parameters such as the layer materials, their thicknesses and the interfaces between them.…”
mentioning
confidence: 99%
“…Characterization by high resolution X-ray diffraction showed that the films were monocrystalline with c-axis oriented perpendicular to the substrate. Well-defined satellite peaks indicated the sharpness of the interfaces and good superlattice periodicity [16]. Cross-sectional transmission electron microscopy demonstrated the continuity of the layers over macroscopic scales, and notably defect-free structures on atomic length scales.…”
mentioning
confidence: 99%
“…In thin film form, it is a better conductor (resistivity of 50 − 100 µΩ · cm) than the manganites (resistivity of 300 − 500 µΩ · cm). Although advances in oxide film growth permit the fabrication of atomically defined layered structures with nanometer scale periodicity [15], the very strict control over stoichiometry and deposition conditions required to produce multilayers remains a significant experimental challenge.In our previous paper [16] we presented the evidence for antiferromagnetic (AFM) interlayer coupling in this system. Here we demonstrate that the initially AFM coupling becomes ferromagnetic (FM) at larger spacer thicknesses and explain this behavior within the RKKY model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A few experimental investigations have explored heterostructures combining manganites and nickelates [5,[15][16][17][18][19][20][21]. Ferromagnetism that is present only at the interface between LaNiO 3 and CaMnO 3 has been observed by x-ray magnetic circular dichroism combined with polarized neutron reflectometry [16].…”
Section: Introductionmentioning
confidence: 99%